Managing the Financial Stability Potential of Crisis Enterprises - Марич, Максим; Korepanov, George; Yatskevych, Inna; Popova, Olha; Shevtsiv, Lyba; Purtskhvanidze, Olga (My University, 2020)
The article deals with the fundamental aspects of managing the financial stability of crisis enterprises. It is revealed that financial stability is an integral element of the financial stability of the enterprise. It is established that the assessment of financial stability potential (rehabilitation potential) is one of the priority tasks of commercial diagnostics of crisis enterprises, the state of which is characterized by the increased probability of bankruptcy and tends to absolute insolvency. In the article, the method of correlation analysis determines the predictive value of the financial stability ratio, which can be used to develop the business strategy of the company or corrective anticrisis management decisions. It is established that the object of management influence of the crisis enterprise should be the potential of financial stability, the settlement of which ensures a positive financial balance of the enterprise.
Keywords: Crisis Enterprise; Crisis Management; Financial Stability Potential; Financial Stability